DIGITAL LITERACY AS A CATALYST FOR ENHANCING PROFESSIONALISM AMONG GUIDANCE AND COUNSELING TEACHERS IN THE DIGITAL ERA - Muchtar Ali Aditama; Dian Purbo Utomo (EDUCATIONE, 2025)
Fundamental changes in education driven by digitalization demand that teachers, including guidance and counseling teachers, possess strong digital literacy to remain professionally competent. This study aimed to analyze the level of digital literacy mastery among guidance and counseling teachers at SMP Negeri 3 Ungaran and to evaluate how these skills support their professional competence. Employing a quantitative descriptive approach with saturated sampling, data were collected from all five guidance and counseling teachers at the school using questionnaires, semi-structured interviews, and documentation studies. The results revealed that the overall digital literacy mastery was high, with Internet searching (75%) and Content evaluation (64%) being the strongest aspects, while Hypertextual navigation and Knowledge assembly both fell into the medium category (59%). These findings suggest that while digital literacy significantly enhances the professional competence of teachers, particularly in accessing and evaluating information, there are still gaps in advanced navigation and integrative knowledge skills—especially among older teachers. The research contributes practical and theoretical insights by highlighting the importance of targeted digital literacy training and adaptive policy development to optimize counseling services. This study is beneficial for education stakeholders seeking to design effective training programs and improve digital integration in school counseling. Future research is recommended to involve larger samples, apply mixed-method approaches, and examine additional dimensions such as digital ethics, wellbeing, and communication skills to further strengthen the digital competence of educators.